2006
DOI: 10.1002/dvdy.20803
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular stimulation causes muscle phenotype‐dependent changes in the expression of the IGFs and their binding proteins in developing slow and fast muscle of chick embryos

Abstract: Insulin-like growth factor (IGF) -1 and -2 and binding protein (IGFBP-2, -4, and -5) expression can be affected by several environmental factors, but the impact of movement on the IGF axis during late embryogenesis has yet to be fully characterized. Movement was promoted in chick embryos during midembryogenesis using 4-aminopyridine (4-AP). The results indicate an increase in IGF-1 (P < 0.01) and a decrease in IGFBP-2 (P < 0.05) mRNA expression in slow muscle of the stimulated group compared with the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This idea fits with the results of Heywood et al, who demonstrated that artificially increasing embryonic movement by in ovo injection of 4-AP leads to increased numbers of myonuclei at ED20 (Heywood et al, 2005). This may be caused by motility-driven changes in IGF expression in the chick, as has been shown following injection of 4-AP (McEntee et al, 2006). However, there are numerous signalling pathways and other growth factors operating in the chick limb during embryonic development such as the FGF (fibroblast growth factor), Shh (Sonic hedgehog), Wnt and BMP (bone morphogenic protein) signalling pathways, with their associated growth factors, which could also be influenced by either temperature or mechanical stretch (reviewed in Duprez, 2002).…”
Section: Temperature and Increased Embryonic Movement Leads Tosupporting
confidence: 89%
See 1 more Smart Citation
“…This idea fits with the results of Heywood et al, who demonstrated that artificially increasing embryonic movement by in ovo injection of 4-AP leads to increased numbers of myonuclei at ED20 (Heywood et al, 2005). This may be caused by motility-driven changes in IGF expression in the chick, as has been shown following injection of 4-AP (McEntee et al, 2006). However, there are numerous signalling pathways and other growth factors operating in the chick limb during embryonic development such as the FGF (fibroblast growth factor), Shh (Sonic hedgehog), Wnt and BMP (bone morphogenic protein) signalling pathways, with their associated growth factors, which could also be influenced by either temperature or mechanical stretch (reviewed in Duprez, 2002).…”
Section: Temperature and Increased Embryonic Movement Leads Tosupporting
confidence: 89%
“…The effects of increased motility on chick development have been less well characterized, although treatment of embryos with the hyperactivity-inducing drug 4-AP led to increased chick body mass at ED15 and ED16, along with increased tibial length at these times, although the differences were not significant at ED20 (Heywood et al, 2005). Similar experiments showed that the balance of insulinlike growth factors (IGFs) can be altered in leg muscles by motility-inducing drugs (McEntee et al, 2006). It is interesting that our temperature experiments have yielded results that closely correlate with the results of inducing motility.…”
Section: Temperature and Embryonic Movementmentioning
confidence: 99%
“…Direct manipulations include the in-ovo injection of growth hormones or factors (e.g. insulinlike growth factor), amino acids, carbohydrates or neuromuscular active drugs into the embryos or its embryonic membranes (Kocamis et al, 1998;Heywood et al, 2005;Uni et al, 2005;McEntee et al, 2006;Pitsillides, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fibre number and oxidative capacity were also increased in the Musculus semitendinosus (ST) of the stimulated chicks before hatching (Heywood et al, 2005). Neuromuscular stimulation caused muscle phenotype-dependent changes in the expression of the IGFs and their binding proteins in developing slow and fast muscle of chicken embryos (McEntee et al, 2006). In addition, in chicken Musculus pectoralis the mRNA expression of the PTEN gene, an inhibitor of cell signalling, increased with age, whereas the protein levels of PTEN and its activity were considerably decreased between E18 and d43 stages, suggesting its involvement in myogenesis (Vaudin et al, 2006).…”
Section: Critical Timings and Mechanismsmentioning
confidence: 99%